Magic realist cinema in East Central Europe - Skrodzka, Aga (Traditions in world cinema., 2012)
Magic Realist Cinema in East Central Europe explores the interlocking complexities of two liminal concepts: magic realism and East Central Europe. Each is a fascinating hybrid that resonates with dominant currents in contemporary thought on transnationalism, globalisation and regionalism. In this critical and comprehensive survey, Aga Skrodzka moves the current debate over magic realism's political impact from literary studies to film studies. Her close textual analysis of films by directors such as Jan Å€vankmajer, Jan Jakub Kolski, Martin Å€ulÃƯk, Ivo Trajkov, Dorota KÄ₉dzierzawska, IldikÃđ Enyedi, BÃ♭la Tarr and Emir Kusturica is accompanied by an investigation of the socio-economic and political context in order to both study and popularise an important and unique tradition in world cinema. The directors' artistic achievements illuminate the connections between a particular aesthetics and the social structure of East Central Europe at a precise moment of contemporary history. Provides the first comprehensive analysis of magic realism in cinema Offers an examination of the post-socialist cinema as representative of the hybridised space and consciousness of East Central Europe Gives a chronological overview of the existing theories of magic realism to the extent in which they apply to globalised visual cultures Considers the cinema of East Central Europe in the context of transnationalism and postcoloniality